DNA profiling and paternity verification in Murrah buffaloes - VIJH, RAMESH KUMAR; SHARMA, UPASNA; GAUR, UMA; GOKHALE, SURESH B (The Indian Journal of Animal Sciences, 2018)
The accuracy of selection for sire’s merit depends upon the number of daughters born to the sire and also the correctness of performance records. The accuracy of records depends on confirmed paternity of the daughters. In this paper, we report paternity confirmation of a large progeny testing program in buffaloes. The work was undertaken in collaboration with BAIF, Pune under National Agricultural Innovation Project. Murrah bulls (12) were selected and around 120,000 buffaloes were inseminated at farmers’ doorsteps. The area of operation was 52 districts of Uttar Pradesh. We targeted 1,000 female calves to be born to each of the 12 sires. The experiment was an effort to develop a reference population for identification of quantitative trait loci for various economic traits in buffaloes using halfsib design. Owing to financial constraints, we targeted 10,000 daughters born to these 12 sires. The DNA was isolated from these daughters. The DNA of sires was also isolated. Since there was no parentage verification kit commercially available for buffaloes, we developed a multiplex PCR reaction consisting of 11 microsatellite markers to confirm the paternity. The correctness of the paternity was established using microsatellite DNA markers and comparison of daughters’ genotype with genotype of sires. The paper reports paternity testing of large reference family. We also developed a software ‘Confirm Paternity’ for comparing the genotypes of daughters with the respective sire. We report paternity correctness of 90.48% in buffaloes under field conditions.